Implementasi Model Pembelajaran Contextual Teaching and Learning dalam Meningkatkan Minat Belajar Siswa Pada Mata Pelajaran Fiqih di MI NW Apitaik - Rulyandi rulyandi (Institut Agma Islam Hamzanwadi NW Lombok TImur, 2020)
Contextual teaching and learning is a learning concept that can help teachers link the material taught with real-world situations and encourage students to make connections between their knowledge and application in life. Basically, contextual teaching and learning is a concept that aims to equip students with knowledge that can be applied flexibly from a problem or from another context so that students' understanding is expected through experience, not just memorizing a material. The research method used is qualitative research with primary and secondary sources, data collection techniques in research by means of observation methods, interview methods and documentation methods. Data analysis was carried out using qualitative data analysis. The results of this study show how the application of the contextual teaching and learning learning model in increasing interest in learning is to develop the idea that students will learn more interestingly when students learn in their own way and find ideas by constructing their own new knowledge and skills. create a learning society. The positive impact of implementing the contextual teaching and learning learning model in increasing interest in learning is that it can develop students' abilities in solving problems, can develop critical, logical and analytical thinking skills and the negative impact of implementing the contextual teaching and learning learning model is the lack of ability to reason